Citizenship Values and Their Implementation in Learning: A Comparative Study Of Schools in Ghana and Indonesia - Gyadu Emmanuel Ofori; Puji Lestari (JESS (Journal of Educational Social Studies), 2026)
This paper will examine the learning and application of citizenship values among learners in the schools in Ghana and Indonesia. The countries consider their citizenship education to be a major factor towards the national development and social peace. The study adhered to the Social Learning Theory, Cultural Theory, and Civic Education Theory and employed qualitative/comparative descriptive design. The data were collected using semi-structured interviews, open-ended questionnaires, classroom observations, and review of documents. The information was given by fifty respondents who consisted of twenty-five students and teachers in Ghana and twenty-five in Indonesia. Our data were examined using the six-step thematic analysis developed by Braun and Clarke and manually. Both Ghana and Indonesia have their values of citizenship shaped by local culture and life in schools. The citizenship as perceived by students in Ghana is largely based on respect to authority, discipline, responsibility, honesty, and obedience which are aspects that reflect on communal traditions and hierarchal norms. Pancasila values that were identified as important by the participants in Indonesia included tolerance, harmony, cooperation (gotong-royong), politeness, and unity in diversity. Teaching styles also varied. Ghanaian educators’ resort to direct moral teaching and disciplinary direction. Indonesian teachers integrate the lessons about citizenship into the school routines, the cooperative learning process as well as into multicultural discussions. Civic conduct is strengthened by school activities, Ghana has assemblies, prefect leadership and Indonesia has piket kelas (class duty) and flag ceremonies. The issues that both nations have in common, however, are peer pressure, the lack of parental support, and excessive use of social media. In short, the study concludes that effective citizenship education occurs when the cultural identity, school culture and teacher role models are aligned and when school, family and communities are working hand in hand. The study provides comparative information on culture-based civic education and supports the evidence-based recommendations to enhance teacher training, curriculum design, school routines, digital citizenship programs, and involvement of the community in Ghana and Indonesia.